A general model of locomotion of brittle stars with a variable number of arms. Issue 162 (8th January 2020) - Wakita, Daiki; Kagaya, Katsushi; Aonuma, Hitoshi
Abstract : Typical brittle stars have five radially symmetrical arms that coordinate to move the body in a certain direction. However, some species have a variable number of arms, which is a unique trait since intact animals normally have a fixed number of limbs. How does a single species manage different numbers of appendages for adaptive locomotion? We herein describe locomotion in Ophiactis brachyaspis with four, five, six and seven arms to propose a common rule for the movement of brittle stars with different numbers of arms. For this, we mechanically stimulated one arm of individuals to analyse escape direction and arm movement. By gathering quantitative indices and employing Bayesian statistical modelling, we noted a pattern: regardless of the total number of arms, an anterior position emerges at one of the second neighbouring arms to a mechanically stimulated arm, while arms adjacent to the anterior one synchronously work as left and right rowers. We propose a model in which an afferent signal runs clockwise or anticlockwise along the nerve ring while linearly counting how many arms it passes through. With this model, the question on how 'left and right' emerges in a radially symmetrical body via a decentralized system is answered.